2019
DOI: 10.1016/j.jep.2019.112028
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of Dongbai-Tonglin-Fang, a Chinese herbal formula, on urinary tract infection in rat model

Abstract: Traditional Chinese Medicine (TCM) has many obvious advantages in the treatment of chronic conditions such as urinary tract infection (UTI). Dongbai-Tonglin-Fang (DBTL), a Chinese herbal formula, has been used for the treatment of UTI for more than 40 years with proven efficacy. However, its mechanism of action is still unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Female rats were water fasted for 24 h and randomly divided into five groups of nine rats each: Saline group, UPEC group, 100-Shi (Shionone) group, 200-Shi group, and 100-LVX (levofloxacin hydrochloride, positive control) group. Levofloxacin is a quinolone antibiotic that is relatively effective against the common pathogens of urinary tract infections, such as Gramnegative rods and Gram-positive cocci [14]. After the rats were anesthetized and their perineum disinfected, the F4 ureteral catheter was passed through the urethra for about 3 cm to reach the bladder, the bladder was emptied of residual fluid, and the prepared bacterial solution (300 μL, 1 × 10 7 CFU/each rat) was pushed into the bladder, after which the urethra was clamped with a paper clip for 2-3 h and then released.…”
Section: Animals and Experimentalmentioning
confidence: 99%
“…Female rats were water fasted for 24 h and randomly divided into five groups of nine rats each: Saline group, UPEC group, 100-Shi (Shionone) group, 200-Shi group, and 100-LVX (levofloxacin hydrochloride, positive control) group. Levofloxacin is a quinolone antibiotic that is relatively effective against the common pathogens of urinary tract infections, such as Gramnegative rods and Gram-positive cocci [14]. After the rats were anesthetized and their perineum disinfected, the F4 ureteral catheter was passed through the urethra for about 3 cm to reach the bladder, the bladder was emptied of residual fluid, and the prepared bacterial solution (300 μL, 1 × 10 7 CFU/each rat) was pushed into the bladder, after which the urethra was clamped with a paper clip for 2-3 h and then released.…”
Section: Animals and Experimentalmentioning
confidence: 99%
“…AKT1 is a key reg-ulator of host cell survival, inflammatory responses, proliferation, and metabolism ( Wiles et al, 2008 ). It was reported that SRC could inhibit TLR4-induced inflammatory cytokines and promote the anti-inflammatory cytokine IL-10, which plays an important role in the treatment of acute and chronic inflammation ( Li et al, 2019 ). Wittmann et al ( Wittmann et al, 2015 ) found that the increased expression of TLRs in patients might result in counter regulation of the host and serve to prevent intestinal inflammation and disease.…”
Section: Discussionmentioning
confidence: 99%